(untitled) (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
Orchids are among the plants with the greatest diversity in the world. Orchids have several specialized structures, such as velamen and cuticles, which help protect them against unfavorable environmental conditions. The anatomical structure of a plant closely relates to how it adapts to its environment. Anatomical characteristics can support data on previously known species, complementing analyses beyond morphological and molecular data related to taxonomic classification. The aim of this study was to examine the variation in leaf anatomical structures among several orchid species found in the Pengelengan Hills, Sukasada, Bali. Sample collection was conducted using exploratory methods, and leaf anatomical structures were analyzed using cross-sectional and peeling methods. Based on the overall research findings, there were variations in the leaf anatomical structures among the five orchid species found in Pengelengan Hills, Sukasada, Buleleng, Bali. Variations were observed in the paradermal sections, showing differences in the arrangement of epidermal tissues. The variations include epidermal cell arrangement, cell shape, stomatal type, and epidermal derivatives. The arrangement of epidermal cells was categorized into two types: aligned and non-aligned. The shapes of epidermal cells observed include pentagonal, hexagonal, elongated, and irregular. The stomatal types observed include tetracytic and paracytic, and epidermal derivatives such as non-glandular trichomes were found in species B. hyacinthoides and M. oblitterata.